2020
DOI: 10.3390/en13051078
|View full text |Cite
|
Sign up to set email alerts
|

Wind Turbine Performance in Very Large Wind Farms: Betz Analysis Revisited

Abstract: The theoretical limit for wind turbine performance, the so-called Betz limit, arises from an inviscid, irrotational analysis of the streamtube around an actuator disk. In a wind farm in the atmospheric boundary layer, the physics are considerably more complex, encompassing shear, turbulent transport, and wakes from other turbines. In this study, the mean flow streamtube around a wind turbine in a wind farm is investigated with large eddy simulations of a periodic array of actuator disks in half-channel flow at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(68 reference statements)
2
4
0
Order By: Relevance
“…With this assumption, we hypothetically divide the flow field into two types of zones; namely the inviscid flow zones, which are analysed using the LMADT neglecting the effect of viscous (or turbulent) mixing, and the viscous flow zones, which are modelled separately to account for the effect of mixing. This approach is also in line with the results of a recent LES study of flow past a periodic array of actuator discs (West & Lele 2020) showing that the effects of inviscid and viscous (turbulent) flow processes are dominant, respectively, in the vicinity of the turbines and in the rest of the flow field.…”
Section: Invsupporting
confidence: 86%
“…With this assumption, we hypothetically divide the flow field into two types of zones; namely the inviscid flow zones, which are analysed using the LMADT neglecting the effect of viscous (or turbulent) mixing, and the viscous flow zones, which are modelled separately to account for the effect of mixing. This approach is also in line with the results of a recent LES study of flow past a periodic array of actuator discs (West & Lele 2020) showing that the effects of inviscid and viscous (turbulent) flow processes are dominant, respectively, in the vicinity of the turbines and in the rest of the flow field.…”
Section: Invsupporting
confidence: 86%
“…As illustrated earlier in figure 1, this approach treats the region around the turbine as an inviscid flow region which is modelled with LMADT, followed by a viscous mixing zone downstream which is modelled separately. This approach is in line with the results of West & Lele (2020) who, in a large-eddy simulation study of flow around an actuator disc, showed that inviscid flow processes dominate around the turbine and viscous processes dominate further downstream. We adopt the same simplification in this analysis as in Ouro & Nishino (2021) that mixing takes place uniformly across the viscous mixing zone and will be defined by a single parameter such that , where is a streamtubes velocity entering the viscous mixing zone, is the average velocity across the whole domain and is the velocity as it exits the viscous mixing zone.…”
Section: Multi-row Resultssupporting
confidence: 90%
“…Hence, by calculating C P for a range of α between 0 and 1, we can find the maximum power coefficient, C Pmax , for a given set of λ/C f 0 , γ and ζ as shown earlier in Figure 1. Note that the exact value of γ is unknown without solving the internal sub-problem for a given wind farm; however, γ = 2 is deemed a good approximation for the prediction of upper limits of power production [13,15]. It is also worth noting that the aforementioned simple theoretical prediction of the upper limit by Miller et al [7] can be reproduced by the present model with λ/C f 0 → ∞, γ = 2 and ζ = 0 (corresponding to an infinitely large and dense wind farm; see [16] for further details).…”
Section: =mentioning
confidence: 99%